2021
DOI: 10.21037/qims-20-349
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional pulsed continuous arterial spin labeling and intravoxel incoherent motion imaging of nasopharyngeal carcinoma: correlations with Ki-67 proliferation status

Abstract: Background: Recurrence and distant metastasis are still the main problems affecting the long-term prognosis of nasopharyngeal carcinoma (NPC) patients, and may be related to the Ki-67 proliferation status. We therefore explored the potential correlation between Ki-67 proliferation status in NPC with the parameters derived from two imaging techniques: three-dimensional pulsed continuous arterial spin labeling (3D pCASL) and intravoxel incoherent motion (IVIM).Methods: Thirty-six patients with pathologically con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…In this study, except for D*, all other parameters showed different degrees of correlation with the Ki-67 index. One possible explanation for this finding is that a high Ki-67 index correlates with increased cell proliferation, which tends to correlate with higher cellular density, more vascular hyperplasia, and more histologic heterogeneity (36)(37)(38).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, except for D*, all other parameters showed different degrees of correlation with the Ki-67 index. One possible explanation for this finding is that a high Ki-67 index correlates with increased cell proliferation, which tends to correlate with higher cellular density, more vascular hyperplasia, and more histologic heterogeneity (36)(37)(38).…”
Section: Discussionmentioning
confidence: 99%
“…Four studies [60,61,63,65] directly investigated the correlation and found a significant inverse association (partial correlation r = −0.253 to r = −0.728; p < 0.001-0.024). In contrast, Wu et al [71] reported a positive but non-significant correlation between ADC mean and Ki-67 (r = 0.238; p = 0.163). An overall effect of COR (−0.37, 95%CI −0.65-0.00; p = 0.051) was calculated; see Figure 4 for the forest plot.…”
Section: Ki-67 Proliferation Indexmentioning
confidence: 83%
“…The associations between the Ki-67 proliferation index and the DWI-metric ADC mean were examined in six studies [60,61,63,65,71,72]. Four studies [60,61,63,65] directly investigated the correlation and found a significant inverse association (partial correlation r = −0.253 to r = −0.728; p < 0.001-0.024).…”
Section: Ki-67 Proliferation Indexmentioning
confidence: 99%
“…Three-dimensional pulsed continuous arterial spin labeling (3D-pCASL) technology safely and non-invasively evaluates tissue perfusion without the use of a contrast agent. Instead, freely diffusing water molecules are used as endogenous contrast agents (9). Diffusion-weighted imaging (DWI) provides insights into the cellular structure and is sensitive to the heat-driven motion of water molecules in tissues (6).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, DWI accurately reflects the state of radiation-induced cell inactivation. Intrixel incoherent motion imaging (IVIM) is a further development of DWI, capable of delivering both diffusion and perfusion imaging results without the need for contrast injection, with the advantage of being completely non-invasive (9,10). IVIM has been widely used in hepatic fibrosis evaluation (11), staging (9,10), efficacy evaluation (12), the differential diagnosis of fibrosis, and monitoring of NPC recurrence following RT (13).…”
Section: Introductionmentioning
confidence: 99%